Abnormal serum phosphorus was associated with the outcome of community-acquired pneumonia - Wang, Si-Qiong; Ma, Cui-Hua; Ma, Chun-Ming; Wang, Rui (Frontiers in Nutrition, 2025)
ObjectiveThe present study aimed to explore the relationship between serum phosphorus levels and outcomes in patients with community-acquired pneumonia (CAP).MethodsThis research was a retrospective, single-center study conducted on adult patients who were hospitalized with CAP at The First Hospital of Qinhuangdao City, Hebei Province, China, between January 2015 and December 2018. The primary outcome was in-hospital mortality. Participants were categorized into four groups: the normal serum phosphorus group (0.81–1.45 mmol/L), the hypophosphatemia group (Grade 1, 0.48–0.80 mmol/L), the hypophosphatemia group (Grade 2, <0.48 mmol/L), and the hyperphosphatemia group (>1.45 mmol/L).ResultsThis study included 1,936 CAP inpatients. The in-hospital mortality rates were 2.5, 4.4, 11.1, and 18.0% in the normal phosphorus group, the hypophosphatemia groups (Grades 1 and 2), and the hyperphosphatemia group, respectively. In the univariate logistic regression analysis, the in-hospital mortality rates for the hypophosphatemia (Grade 2) and hyperphosphatemia groups were 4.892 (95% CI: 1.410–16.969, p = 0.012) and 8.572 times (95% CI: 4.912–14.960, p < 0.001) higher, respectively, compared to the normal phosphorus group. After adjusting for confounding factors, hypophosphatemia (Grade 2) (OR = 3.715, 95% CI: 1.013–13.633, p = 0.048) and hyperphosphatemia (OR = 5.221, 95% CI: 2.747–9.924, p < 0.001) were identified as independent correlative factors associated with in-hospital mortality.ConclusionHyperphosphatemia and severe hypophosphatemia upon admission were associated with increased in-hospital mortality in CAP inpatients.